2010
DOI: 10.1063/1.3455848
|View full text |Cite
|
Sign up to set email alerts
|

Island shape controls magic-size effect for heteroepitaxial diffusion

Abstract: Lattice mismatch of Cu on Ag(111) produces fast diffusion for special "magic sizes" of islands. A sizeand shape-dependent reptation mechanism is responsible for low diffusion barriers. Initiating the reptation mechanism requires a suitable island shape, a property not considered in previous studies of 1D island chains and 2D closed-shell islands. Shape determines the dominant diffusion mechanism and leads to multiple clearly identifiable magic-size trends for diffusion depending on the number of atoms whose bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Using low-temperature scanning tunneling microscopy (STM), we have previously shown that larger clusters have surprisingly low diffusion barriers and a novel dislocation mechanism that is related to the ~12% lattice mismatch for Cu on Ag(111) [25,26]. Here, we show that Cu trimers diffuse large distances following their formation.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Using low-temperature scanning tunneling microscopy (STM), we have previously shown that larger clusters have surprisingly low diffusion barriers and a novel dislocation mechanism that is related to the ~12% lattice mismatch for Cu on Ag(111) [25,26]. Here, we show that Cu trimers diffuse large distances following their formation.…”
Section: Introductionmentioning
confidence: 73%
“…The extremely low diffusion barrier for the linear trimer, combined with the preference for this structure during nucleation, make the trimer an extremely important contributor to mass transport for Cu on Ag(111). The effects of lattice mismatch are manifest in the observed directions of hopping and rotation that require intermediate steps involving trimers of mixed fcc-hcp character that shorten Cu-Cu bonds to relieve strain, in a one-dimensional analog of the misfit-dislocation mechanism responsible for the low diffusion barriers of larger Cu clusters on Ag(111) [25,26]. Because the novel diffusion phenomena for both small and large clusters of Cu on Ag(111) result from lattice mismatch, it is likely that similar behavior will occur in other heteroepitaxial systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyse the eect of the mobility of small islands on the growth of the large island we consider that islands diuse as clusters. The eects of cluster diusion on the island size distribution have been reviewed for the case of irreversible growth of compact islands on a 2D substrate, and several mechanisms for the diusion of large particles on solid surfaces were proposed [74][75][76][77][78][79]. In most cases, scaling arguments predict that the coecient of particle diusion decays as a power law with particle sizes n ∼ µ −…”
Section: Small Island Capturementioning
confidence: 99%